1978
DOI: 10.1080/03014467800002861
|View full text |Cite
|
Sign up to set email alerts
|

Handedness, hand-clasping and arm-folding in Israeli males

Abstract: Comparative analysis of handedness, hand-clasping and arm-folding frequencies in four groups of adult Israel Jewish males of East European origin (N=562), Central European origin (N=165), Middle Eastern origin (N=191), and North African origin (N=163), indicates a significant similarity between the groups. A high percentage of left-handed individuals was observed in all groups except the Middle Eastern one. Right-hand clasping and left arm-folding predominated in all but the Central European group in which lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Cohort effects on handedness have been reported in several countries, and most studies show an increase in left-handedness. For example, Kobyliansky, Micle, and Arensburg (1978) showed that 15.5% of Israeli-born subjects were left-handed as compared with only 5.9% of the members of a previous generation who were not born in Israel. Fleminger et al (1977) found in a British sample that left handedness for writing was inversely related to age, ranging from 2.9% among 56–64 year olds (born in 1912–1922) to 10.8% among 15–24 year olds.…”
Section: Resultsmentioning
confidence: 99%
“…Cohort effects on handedness have been reported in several countries, and most studies show an increase in left-handedness. For example, Kobyliansky, Micle, and Arensburg (1978) showed that 15.5% of Israeli-born subjects were left-handed as compared with only 5.9% of the members of a previous generation who were not born in Israel. Fleminger et al (1977) found in a British sample that left handedness for writing was inversely related to age, ranging from 2.9% among 56–64 year olds (born in 1912–1922) to 10.8% among 15–24 year olds.…”
Section: Resultsmentioning
confidence: 99%
“…Rhoads and Damon [28] suppose that hand clasping and arm folding are not associated with one another, and arm folding is not associated with either handedness or sex; however, they do show an age association. Kobyliansky et al [29] note that L-tendencies in both actions are pronounced in left-handers and ambidextrous individuals, while right-handers demonstrate right hand-clasping and left arm-folding. Also, although the manifestations of these traits vary within each group (left-handed, right-handed, and ambidextrous people), these authors believe that these traits are suitable for detecting left-handedness.…”
Section: Resultsmentioning
confidence: 99%
“…HCL and ARMF showed no association with radiologically measured digit ratios. [1,17,21,29]. In our study, the digit ratio was assessed by radiographic evaluation, an infrequent way of assessing digit ratios, but which has been previously used in several studies [20,24,27,34].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that approximately 35% of right-handers and approximately 57% of left -handers, were left eye dominant [2]. Th ere are ongoing controversies about the association between HDD and HCL and between HCL and ARMF [11,17,25,32,33]. Prevalence of laterality indices in the Chuvashian population was previously described [11] It has been suggested that the index to ring the digit ratio or 2D:4D ratio is a biomarker of testosterone [24,31] or both androgen and estrogen [18,40] exposure during early intra-uterine life.…”
mentioning
confidence: 99%